Rethinking the Individualized Education Plan process: voices from the other side of the table. Issue 3 (16th March 2017) - MacLeod, Kate; Causton, Julie N.; Radel, Mary; Radel, Patrick
Abstract: Parent involvement in the process of creating an Individualized Education Plan (IEP) is authorized under the Individuals with Disabilities Education Act, a federal law in the United States that ensures children with disabilities have the opportunity to receive a free appropriate public education alongside their peers without disabilities in the least restrictive environment. Yet much research has shown that parents often feel like outsiders during the process. To understand parent perspectives about how educators might help make the IEP process more collaborative and inclusive, this study collected qualitative data from 35 parents of students with disabilities who have worked to develop an IEP with a school team. Our findings provide insight into parent experiences and evidence that parents have many suggestions for how educators can improve the IEP process. In our discussion section, we provide educators with strategies to address parent suggestions.